RISK OF ADENOCARCINOMA IN BARRETT’S ESOPHAGUS - Serha, T.V.; Kuryk, O.H.; Yakovenko, V.O.; Tkachenko, R.P. (World of Medicine and Biology, 2020)
The total of 7396 videoesophagogastroscopy cases were analyzed. The presence of metaplastic columnar epithelium of esophagus was found in 2910 patients (39.4%) at pathohistological examination. The gastric metaplasia was evaluated in 876 cases (11.9%), the specialized intestinal metaplasia without dysplasia - in 1970 (26.6%), the low-grade dysplasia - in 48 (0.65%), the high-grade dysplasia - in 16 (0.22%). Esophageal adenocarcinoma was evaluated in four patients (0.05%, CI 0.01 - 0.12%). Low probability of esophageal adenocarcinoma formation in all types of metaplasia was demonstrated. Оnly the presence of dysplasia of metaplastic epithelium should cause increased alertness for the occurrence of esophageal adenocarcinoma. Exaggerated value of Barrett’s esophagus may result in additional traumatization of mucosa, increase the risk of bleeding and stenosis.